2020
DOI: 10.3389/fneur.2020.604299
|View full text |Cite
|
Sign up to set email alerts
|

Lockdown During COVID-19 and the Increase of Frailty in People With Neurological Conditions

Abstract: Governments around the globe have introduced quarantine, lockdown, and mandatory isolation to slow the transmission of COVID-19. These public health and policy measures aim to protect the public and vulnerable people. This perspective paper argues that the impacts of lockdown (such as social disconnection, reduced exercise, and fewer physiotherapy treatments) may be amplified for people with neurological conditions with subsequent increases in frailty. The paper outlines why this may occur, and explores how ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 56 publications
(69 reference statements)
0
17
0
Order By: Relevance
“…Although the lockdown on vulnerable populations was an essential step, some critical aspects of social isolation and primary service interruption have recently been highlighted [4,5]. Indeed, these aspects negatively reflect physical, cognitive, and mental health outcomes for people with chronic neurological conditions, who need extensive and continuous care, regular physical activity, and daily routine and balance [6].…”
Section: Introductionmentioning
confidence: 99%
“…Although the lockdown on vulnerable populations was an essential step, some critical aspects of social isolation and primary service interruption have recently been highlighted [4,5]. Indeed, these aspects negatively reflect physical, cognitive, and mental health outcomes for people with chronic neurological conditions, who need extensive and continuous care, regular physical activity, and daily routine and balance [6].…”
Section: Introductionmentioning
confidence: 99%
“…Pelicioni et al [ 35 ] have reported that individuals with CND such as stroke, PD, and MS are vulnerable to complications of illness because they did not receive the necessary care, especially during forced lockdown, in a review which is evaluating data from several countries. In addition to the results of Pelicioni et al [ 35 ], our data indicated that the QoL was lower especially in the group with disrupted treatment.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that living alone, a lower level of education, not having children, or having >2 children, living in urban areas, female gender, age, past psychiatric history, substance abuse, and poor self-care are factors associated with depression, anxiety, and stress in various studies [ 26 , 27 , 29 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. In our study, because the percentage of people living alone is low (6%), no interpretation could be made in terms of PTSD risk.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, studies have shown increased frailty, worsening of symptoms, or accelerated progression of disease in patients with Parkinson's, multiple sclerosis, or adults with cognitive impairment and dementia. 28 Further, studies have shown worsening of neurological condition in children with existing neurological disorder, as well as worsening of papilledema in patients with new or existing idiopathic intracranial hypertension. 29,30 For other neurological diseases, such as pediatric epilepsy, remote consultations and telemedicine emerged as feasible avenues to continue following patients in the elective setting while avoiding unnecessary visits and exposure to SARS-CoV-2.…”
Section: Neurosurgical Practicementioning
confidence: 99%